Poland–China Educational Cooperation before the COVID-19 pandemic: University of Łódź Case Study - Kowalski, Bartosz (Rethinking Asia in World Politics, 2023)
This article examines the University of Łódź’s educational cooperation before the outbreak of the COVID-19 pandemic. By analyzing educational and research interactions within the broader framework of Poland-China bilateral relations, both from historical and contemporary perspectives, the author argues that the intensity of contacts between University of Łódź and Chinese counterparts has often been dependent upon fluctuations in the political relations between the two countries and that despite initial enthusiasm the cooperation is now heading on more realistic tracks.